Hang the moon : a novel - Bellefleur, Alexandria (Avon, an imprint of HarperCollinsPublishers, 2021)
When his sister's best friend, also his longtime crush, unexpectedly visits Seattle, Brendon attempts to woo her with ideas from his favorite romantic comedies.